(untitled) (Third Sector Social Economic Review, 2017)
In Turkey, there are 552 fisheries cooperatives and 30,817 fishermen associations organized in 68 provinces within the marine and inland water resources. Istanbul is a pioneer in the country with 48 cooperatives and over four thousand fishing associations. In Istanbul there are 21 fisheries cooperatives operating in the Marmara Sea, the Black Sea and the Bosporus. The largest number of cooperatives and partners can be found in the Sarıyer district, whereas Maltepe has the least number.